Advances in sustainable thermosetting resins: From renewable feedstock to high performance and recyclability. (February 2021) - Liu, Jingkai; Wang, Shuaipeng; Peng, Yunyan; Zhu, Jin; Zhao, Weiwei; Liu, Xiaoqing
Abstract: In polymer science and industry, the important role of thermosetting resin is well-recognized. However, most thermosets suffer from the overdependence on petroleum resource and in addition are linked to environmental concerns. The development of sustainable thermosetting resins thus has become an objective of contemporary research. Addressing this need generally requires renewable feedstocks, satisfied comprehensive properties, and long service life or recyclability. Herein, a systematic overview regarding recent advances in sustainable thermosetting resins is provided. Firstly, the origins and access of bio-based platform compounds successfully applied in the bio-based thermosetting resins are being discussed. Subsequently, the synthesis, structure-property relationships, and methodologies for the functionalization of three typical bio-based thermosets, including benzoxazine, epoxy resin and unsaturated polyester, are being reviewed. Finally, strategies for the recycling of bio-based thermoset waste products are being presented. The objective of this work is not only to summarize the recent progress on sustainable thermosets, but also help us understand them more deeply and widely in a short time, so as to promote their faster development. Graphical abstract: Image, graphical abstract